Supercontinuum Generation for Ultrahigh-Resolution OCT via Selective Liquid Infiltration Approach - Sorahi-Nobar, Mojtaba; Maleki-Javan, Alireza (Společnost pro radioelektronické inženýrství, 2018)
In this paper, we apply liquid infiltration approach for supercontinuum generation (SCG) in photonic crystal fiber (PCF) in which by selectively infiltrating three air holes of PCF, a near zero dispersion is obtained that is a key parameter for SCG. Our numerical results show that by launching a very short input optical pulse of 50 fs in normal dispersion regime with wavelength centered about 700 nm, into 50 mm PCF infiltrated by ethanol, broadband, coherent and ripple free SC as wide as 1000 nm will be achieved that covers the visible light and a part of near infrared spectra used for ultrahigh-resolution optical coherence tomography.
Keywords: Photonic crystal fiber (PCF); optical coherence tomography (OCT); Liquid infiltration; supercontinuum generation; normal dispersion.